Vine Physiology, Yield Parameters and Berry Composition of Sangiovese Grape under Two Different Canopy Shapes and Irrigation Regimes - Gabriele Valentini; Chiara Pastore; Gianluca Allegro; Riccardo Mazzoleni; Fabio Chinnici; Ilaria Filippetti (Agronomy, 2022)
Vitis vinifera L. adapts well to a scarce availability of water in the soil. However, in recent decades, the combination of thermal stress with prolonged water scarcity could have dramatic consequences on the vine’s physiological status. In this paper, we evaluated the effects of two canopy shapes and two irrigation regimes at veraison on vine physiology, yield parameters and grape composition through biochemical and molecular approaches. The water shortage strongly influenced the physiology of Sangiovese only when the stress was moderate to severe. Neither the water stress limited to veraison nor the canopy shape were able to influence the yield parameters and sugar content, and a strong induction of the expression of the genes involved in the biosynthesis of anthocyanins was recorded only in conditions of moderate-to-severe stress. This phenomenon led to an increase in the anthocyanin content in berry skins until the end of veraison. Conversely, no significant effects occurred in terms of biochemical and molecular performance after re-watering and at harvest. Though the shape of the canopy could play a role only under elevated temperature and prolonged drought, severe water stress can affect the vine physiology and berry ripening during the veraison stage.